Optimizing the zymogram of exogenous proteases in broiler diets by in vitro simulated gastrointestinal digestion and response surface methodology - Yang Liu; Shijie Liu; Fengming Chen; Shengli Liu; Qian Lin; Qiuzhong Dai (Scientific Reports)
Abstract Low protein digestibility causes intestinal flora imbalance, wet litter, and nitrogen pollution. The present study aimed to explore the optimal zymogram of exogenous acid protease (ACP), neutral protease (NEP), alkaline protease (ALP), and keratinase (KEA) in corn-soybean based diets for broilers. The hydrolysis performances of the four monocomponent proteases were presented by enzymatic hydrolysate gross energy (EHGE) and improved dry matter digestibility (IDMD), which were tested via the in vitro simulated digestion method. The optimal combination of the four proteases was predicted by the response surface method. Results showed that the optimal zymogram for 1 to 3-wk-old broiler diet was 1.80 U/g ACP, 2.30 U/g NEP, 29.30 U/g ALP, and 2.80 U/g KEA, and the EHGE and IDMD reached 94.65 Cal/g and 2.54%. The optimal zymogram for 4 to 6-wk-old broiler diet was 1.50 U/g ACP, 1.90 U/g NEP, 31.53 U/g ALP, and 3.10 U/g KEA, and the EHGE and IDMD reached 92.29 Cal/g and 2.47%. The performances of the predicted optimal zymogram were further verified by in vitro simulated digestion method. Collectively, the combined use of four proteases could improve the protein digestibility in broiler diets, which had better effect than monocomponent protease.